The development of the vanderbilt pediatric dizziness handicap inventory for patient caregivers (DHI-PC). Issue 10 (October 2015) - McCaslin, Devin L.; Jacobson, Gary P.; Lambert, Warren; English, Lauren N; Kemph, Alison J
Abstract: Purpose: The purpose of the present investigation was to develop a psychometrically sound dizziness disability/handicap outcome measure for use with a pediatric population between 5 and 12 years of age. Methods: Items comprising Phase 1 of the DHI-PC were created based on reports from parents, providers and patients. This version was administered to the caregivers (mean age 31.6 years, sd 5 years, 74 female) of 86 pediatric patients (mean age 9 years, sd = 2.83 years, 45 female). The caregiver's responses to each item were limited to "yes" (scored as 4 points), "sometimes" (scored as 2 points) or "no" (scored as zero points). Results: A factor analysis for Phase 1 of the scale showed there to be a single factor (eigenvalue of 11.51) that explained 29% of the total variance. The results of Cronbach's alpha analysis enabled us to eliminate 15 items reducing the scale to 25 items (i.e. Phase 2 of the DHI-PC). Following elimination of the items with low item-total coefficients, the second phase of the DHI-PC was administered to 56 legal guardians (mean patient age 8 years, sd 4.65 years, 37 female). The analysis of this data again showed there to be a single factor (eigenvalue of 8.30) that explained 33% of the variance. Four items demonstrated item-total correlations less than 0.40. The final version of the DHI-PC has 21 items and a maximum score of 84%. Short-term test–retest reliability (i.e. three week interval between test and retest) of this DHI-PC was assessed for a subset of 10 patients (caregivers, mean age 38 years, sd = 7 years, 10 female). The results indicated the short-term, test–retest reliability to be strong ( r = 0.98, p ≤ 0.001). Conclusion: The DHI-PC represents a new tool for assessing the impact of pediatric dizziness on the patient (as viewed through the perspective of the caregiver). This tool may be incorporated into the comprehensive evaluation of children suffering from dizziness.